1978
DOI: 10.1042/cs0540403
|View full text |Cite
|
Sign up to set email alerts
|

Structure—Activity Relations of the Fibrinolytic Response to Vasopressins in Man

Abstract: 1. The systemic plasminogen activator response has been examined after intravenous infusion of the following peptides related to neurohypophyseal hormones in approximately equimolar dosages into informed, consenting human volunteer subjects: (a) the natural nonapeptides: lysine-and argininevasopressin, oxytocin and arginine-vasotocin, (b) the N-and C-terminal tripeptide fragments of vasopressin and (c) four vasopressin analogues without pressor activity, altered at the jV-terminus, the disulphide bridge and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2

Year Published

1980
1980
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
1
23
2
Order By: Relevance
“…The drug has minimal vasoactive properties, yet it has been reported to be more effective than adrenaline and lysine-or arginine-vasopressin in mobilising endothelial molecules [24]. Small, though significant, changes of blood pressure and heart rate, together with marked flushing, were observed in all subjects in this study, suggesting that DDAVP is active at some vascular sites (i. e. the skin of the face, neck and chest) and that the endothelium may be differentially affected by the action of the analogue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug has minimal vasoactive properties, yet it has been reported to be more effective than adrenaline and lysine-or arginine-vasopressin in mobilising endothelial molecules [24]. Small, though significant, changes of blood pressure and heart rate, together with marked flushing, were observed in all subjects in this study, suggesting that DDAVP is active at some vascular sites (i. e. the skin of the face, neck and chest) and that the endothelium may be differentially affected by the action of the analogue.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma levels of von Willebrand factor (vWF), a glycoprotein synthesized and stored in the endothelial cells [1], are increased in patients with diabetic microangiopathy [24]. This abnormality is associated with hyperperrneability of the retinal capillaries to fluorescein [5] and could result from widespread endothelial damage in diabetes.…”
mentioning
confidence: 99%
“…The mechanism for the action of DDAVP on PGI2 production is not en tirely clear. Previous in vitro studies have shown DDAVP to have a direct stimulatory effect on PGI2 production from arterial tissue [7], while there is mounting evidence that the effect of DDAVP on FVIIR:Ag release is mediated via a secondary messenger [20,21]. In the absence of any change in TxB2 levels following DDAVP, the stimulatory effect on PGI2 production may be mediated through an endothelial cell receptor rather than a gen eral activation of the arachidonic acid cas cade.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, it has been suggested that these receptors may be located in the central nervous system. Cash et al [27] hypothesized that vasopressin-like molecules may be hu moral messengers acting on a cephalic center, which may in turn release a second messenger that stimulates the endothelial cells indirectly. However, this putative sec ond messenger has not been identified in bovine pituitary and hypothalamic extracts [28].…”
Section: Discussionmentioning
confidence: 99%